2011
DOI: 10.1136/bcr.01.2011.3712.corr1
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin lymphoma presenting with numb chin syndrome

Abstract: There is an error in the author list of this article. The spelling of the second author's name 'Rimas Luka' is incorrect and it should be the following correct spelling, 'Rimas Lukas'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There have been several other case reports of NCS where there has been no evidence of a metastatic lesion in the mandible or base of skull on imaging. 18,20 It is important to remember that lack of radiographic changes cannot exclude the possibility of small metastatic lesions in the jaw. 21 Friedrich reported a case of tumour infiltration of the inferior alveolar nerve inside the mandibular canal that was found on surgical exploration after a negative CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several other case reports of NCS where there has been no evidence of a metastatic lesion in the mandible or base of skull on imaging. 18,20 It is important to remember that lack of radiographic changes cannot exclude the possibility of small metastatic lesions in the jaw. 21 Friedrich reported a case of tumour infiltration of the inferior alveolar nerve inside the mandibular canal that was found on surgical exploration after a negative CT scan.…”
Section: Discussionmentioning
confidence: 99%
“… 2,15 Current expert opinion is that NCS of unknown cause is to be treated as suspected malignancy until proven otherwise. 18 …”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] In rare cases, a numb chin syndrome can be the only symptom, which should always be considered as a sign of malignancy. [ 8 ] Radiological signs are expansion of the bone, enlargement of the mandibular canal and mental foramen, and alveolar bone loss. In advanced stages, bone destruction can occur, appearing as a solitary defect or resorption of the alveolar bone margin, which resembles periodontitis or a periodontal abscess.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested a possible mechanism of microscopic seeding of the malignant cell in the nerve, which is not visible in radiological imaging. This could be another mechanism causing numb chin syndrome [11]. …”
Section: Discussionmentioning
confidence: 99%